A 40-Year-Old Patient With Autoimmune Hepatitis And Portopulmonary Hypertension With Miliary Tuberculosis. Challenges Of Drug Treatment: A Case Report (2016)
Autoimmune hepatitis (AIH) is a rare disease with prevalence of 1.07-1.9 per 100.000 in Europe affects preferentially females and is characterized by idiopathic hepatitis, increased seric gamma globulins, and circulating non-organ-specific antibodies and the comerstone of the therapy is immunosuppression. The complications of AIH are the same as in any other chronic liver disease including hepatopulmonary syndrome (HPS) and portopulmonary hypertension (PPH). We discuss a case report of PPH and milliary tuberculosis (tb) and interactions between sildenafil and antituberculosis treatment.